Digitalization of decentralized supply chains during global crises - Taghipour, Atour, 1974- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book provides new approaches of digitalization of decentralized supply chains and industries to help researchers, educators, consultants and practitioners to deal with global crises and to improve the global performance of supply chains"--